Effects of microwave heating in nanolaminated Nb2GeC synthesis. Issue 14 (1st November 2016) - Bortolozo, Ausdinir D.; Cremasco, Alessandra; Floriano, Ricardo; Contieri, Rodrigo J.
Abstract: MAX phases are a class of ternary compounds, known to exhibit combined properties of ceramics and metals. In this study, we have used the microwave (MW) and conventional (CV) heat treatments in order to synthesize the Nb2 GeC phase starting from the mixtures of raw materials (Nb, Ge and C). The results of a detailed microstructural characterization that includes X-ray diffraction (XRD) with Rietveld refinement and scanning electron microscopy (SEM) of MW and CV treated samples are reported. The XRD patterns followed by Rietveld analysis revealed that the MW sample presents 93 vol% of Nb2 GeC phase after 48 h of processing while the CV sample has taken 240 h to attain similar results. Rietveld analysis confirmed that the Nb2 GeC phase has a hexagonal structure with P6 3 /mmc space group and lattice parameters of a =0.323±0.005 nm and c =1.256±0.005 nm. The crystallite size was estimated by using the Williansom-Hall method being about 75 nm and 62.5 nm for the processed samples after 240 h to CV and MW sample, respectively. SEM analysis showed the presence of a more refined microstructure and relatively lowers porosity for MW sample in comparison with CV sample. These results have indicated the high potential of microwave heating to produce MAX phases in a shorter processing time when comparing with conventional processing routes.